Simulation of 1x2 OTDM router employing symmetric Mach-Zehnder switches - Ghassemlooy, Z.; Ngah, R. (2005)
In high-speed all-optical time division multiplexed (OTDM) routers it is desirable to carry out data routing, switching, clock recovery and synchronisation in the optical domain in order to avoid the bottleneck due to optoelectronics conversion. The authors propose an optical switch based on all-optical symmetric Mach–Zehnder (SMZ) switching and investigate its characteristics. The proposed switch is to be used as a building block for a simple 1x2 OTDM router for asynchronous OTDM packet routing, where clock recovery, address recognition and payload routing are all carried out in the optical domain. Simulation and numerical results demonstrate that clock recovery, address recognition and payload routing are possible with small amounts of crosstalk. Also presented are simulation results for bit error rate (BER) performance for the 1x2 router. For a BER of 10e-9 the receiver sensitivity is -26 dB compared with baseline detection without a router of -38 dB. The proposed router displays great potential for use in ultrahigh- speed OTDM networks.